Satanic Ritual Abuse and Legend Ostension - Ellis, Bill (Journal of psychology and theology, 1992)
Folklorists have proposed the term ostension to describe real-life actions that are guided by a pre-existing legend. In its purest form, ostension is the literal acting out of a story in real life. An example might be if a group of child abusers, hearing rumors about Satanic Ritual Abuse (SRA), were to change their modus operandi to include some of the atrocities mentioned, to confuse children and make prosecution difficult. Such a situation is possible, but folklore research suggests that it is far rarer in reality than three other forms of ostension: pseudo-ostension, quasi-ostension, and proto-ostension. In pseudo-ostension, individuals fabricate details of SRA to lead others to believe that satanists are responsible, when the child abuse has a different nature and motivation. In quasi-ostension, over-anxious authorities may overinter-pret evidence to make it coordinate with notions of “classic” SRA, when in fact the situation is less clear-cut. Finally, in proto-ostension, individuals may, for a variety of sincere reasons, claim events of other people as their own personal experiences. Analysts of the SRA controversy should be careful not to commit themselves to extreme positions of belief or disbelief; facts can become narrative and narrative can become fact.